Development of LKPD differentiated on statistical material - Anggraeni, Candra; Bella, Anastasya; Inganah, Siti (Jurnal Pendidikan Matematika RAFA, 2024)
This research aims to develop a valid and practically differentiated LKPD that can be used by secondary school students when learning statistics in a data-focused format. This research uses the ADDIE (Analysis, Design, Development, Implementation and Evaluation) method. The tools of this research into LKPD are differentiated based on statistical materials, validation models and practical tests of LKPD by teachers and     students. The research process begins with initial analysis through expert validation, review, practical testing, and small and large-scale trials. The results of the development of differentiated E-LKPD to support students' mathematical competencies by subject experts are worth testing with revisions based on reviewer suggestions. The results showed 78% for validation of the material, 89% for verification by media experts, 83.3% for practical application by teachers and 86% for field test results by students. The carried out development of educational materials in the differentiated format of E-LKPD conforms to the correct standards and is also practical for use by high school students in statistical material.